On Some Generalizations of Commuting Mappings - Mohammad Ali Alghamdi; Stojan Radenović; Naseer Shahzad (Abstract and Applied Analysis)
It is shown that occasionally JH operators as well as occasionally weakly biased mappings reduce to weakly compatible mappings in the presence of a unique point of coincidence (and a unique common fixed point) of the given maps.